An epidemiological study of rates of illness in passengers and crew at a busy Caribbean cruise port - Cathy Ann Marshall; Euclid Morris; Nigel Unwin (BMC, 2016)
Abstract Background The Caribbean has one of the largest cruise ship industries in the world, with close to 20 million visitors per year. The potential for communicable disease outbreaks on vessels and the transmission by ship between countries is high. Barbados has one of the busiest ports in the Caribbean. Our aim was to describe and analyse the epidemiology of illnesses experienced by passengers and crew arriving at the Bridgetown Port, Barbados between 2009 and 2013. Methods Data on the illnesses recorded were extracted from the passenger and crew arrival registers and passenger and crew illness logs for all ships and maritime vessels arriving at Barbados' Ports and passing through its territorial waters between January 2009 and December 2013. Data were entered into an Epi Info database and most of the analysis undertaken using Epi Info Version 7. Rates per 100,000 visits were calculated, and confidence intervals on these were derived using the software Openepi. Results There were 1031 cases of illness from over 3 million passenger visits and 1 million crew visits during this period. The overall event rate for communicable illnesses was 15.7 (95 % CI 14.4-17.1) per 100,000 passengers, and for crew was 24.0 (21.6-26.6) per 100, 000 crew. Gastroenteritis was the predominant illness experienced by passengers and crew followed by influenza. The event rate for gastroenteritis among passengers was 13.7 (12.5-15.0) per 100,000 and 14.4 (12.6, 16.5) for crew. The event rate for non-communicable illnesses was 3.4 per 100,000 passengers with myocardial infarction being the main diagnosis. The event rate for non-communicable illnesses among crew was 2.1 per 100,000, the leading cause being injuries. Conclusions The predominant illnesses reported were gastroenteritis and influenza similar to previous published reports from around the world. This study is the first of its type in the Caribbean and the data provide a baseline for future surveillance and for comparison with other countries and regions.